Imaging and pathological features of gastric lesion of immunoglobulin G4-related disease: A case report and review of the recent literature. Issue 2 (4th March 2019) - Inoue, Dai; Yoneda, Norihide; Yoshida, Kotaro; Nuka, Hiromi; Kinoshita, Jun; Fushida, Sachio; Toshima, Fumihito; Minami, Tetsuya; Takahira, Masayuki; Hamaoka, Shoko; Ikeda, Hiroko; Gabata, Toshifumi; et al.
Abstract: We describe a 67-year-old man with immunoglobulin G4-related disease (IgG4-RD) presenting with optic neuropathy, dacryoadenitis, periaortitis, retroperitoneal fibrosis, and a gastric mass-like lesion. A mass-like lesion measuring 52 × 40 mm in the antrum of the stomach was found incidentally through whole-body screening for other organ involvement of IgG4-RD using contrast-enhanced computed tomography (CT). Histology of the stomach revealed that the lesion was also IgG4-related and was located in the submucosal layer extending to the subserosal region. This case suggests that the stomach can also be a site of involvement of IgG4-RD.